Some classes of almost convergent paranormed sequence spaces defined by orlicz functions - Isik, Mahmut (Warsaw University, 2012)
In this paper we define ? ?(M, p, ?, q, s), c(M, p, ?, q, s) and c0(M, p, ?, q, s), the sequence spaces on a seminormed complex linear space, using an Orlicz function. We give various properties and some inclusion relations on this space.
Keywords: Invariant mean; Orlicz function; Seminorm